Potential verbal attacks in a television political talk show: A case of a host’s questioning - Sri Handayani (Indonesian Journal of Applied Linguistics, 2023)
This study examined potential verbal attacks in questioning delivered by a host of a political talk show in Indonesia. It aims at describing a realization of the potential verbal attacks in questioning and identifying the patterns which provides the resource persons with an awareness of the verbal attacks delivered by the host to appropriately respond to them. The data were taken from the host questioning items from a political talk show dialogue ‘Mata Najwa’ in five different political topics entitled ‘Adu Kuat di Demokrat’, ‘Berebut Tahta di Tengah Wabah’, ‘Beres-Beres Kursi Menkes’, ‘Gaduh Tiga Periode’, and ‘Kritik Tanpa Intrik’. The research applied a qualitative method with a descriptive design by employing Elgin’s definition and verbal attack pattern, presuppositions, and the context in questioning referring to the information triggered by certain linguistic constructions of the participant's speech event. The results indicated that the host's questioning behavior during the political talk show potentially tends to result in verbal attacks. The realization of potential verbal attacks resulted in the form of interrogative sentences initiated by wh-question words, modalities, conjunctions, and auxiliary words and affirmative (statement) as a question that was getting more complex depending on the depth of information and presuppositions hidden in the host questioning. The complexity of the attack patterns used by the host affects the strategy used to break, reject, or attack the opinion or argument by countering, judging and criticizing, and denying the resource person's responses.